Answer:
e^2 -7 = x
Step-by-step explanation:
2=ln(x+7)
Raise each side to the base of e
e^2 = e^ln (x+7)
The e^ln cancel
e^2 = x+7
Subtract 7 from each side
e^2 -7 = x +7-7
e^2 -7 = x
Answer:
5
Step-by-step explanation:
This illustrates the Remainder Theorem. If a polynomial f(x) is divided by x−a , the remainder is the constant f(a) , and f(x)=q(x)⋅(x−a)+f(a) , where q(x) is a polynomial with degree one less than the degree of f(x) . Synthetic division is a simpler process for dividing a polynomial by a binomial.
Answer:
sorry dont know
Step-by-step explanation:
Answer:
try 20 percent, im probably wrong cuz im stupid but that might be it
Step-by-step explanation:
not recommended to use my answer
Answer:
1.1 Factoring: x2-44
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
Proof : (A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
Note : AB = BA is the commutative property of multiplication.
Note : - AB + AB equals zero and is therefore eliminated from the expression.
Check : 44 is not a square !!
Step-by-step explanation: